Development of a piping system for a flow visualization water tunnel / Muhammad Aimi Aireez Zamir and Norhisyam Jenal - Zamir, Muhammad Aimi Aireez; Jenal, Norhisyam (School of Mechanical Engineering, 2022)
A water tunnel is an experimental mechanism used to test the hydrodynamic behaviour of the water stream when flowing inside a chamber and when subjected to different submerged bodies. Fluid mechanics is one of the courses that introduce the concept of fluid flow. However, no water tunnels are available for the students in the faculty at this moment. Due to this concern, there is a need for a small-scale water tunnel that can be used to assist the student in understanding fluid flow behaviour. The objective of the project is to design and fabricate a piping system for a flow visualisation water tunnel. This is one of the three sections done by different students which combined into a working water tunnel prototype. The 3-dimensional design was done by using computer-aided design software and some of the fabrication processes involved in this project were cutting, grinding, and drilling. The finished piping system is equipped with a 370 watts electric pump able to flow water at a velocity of 0.67 m/s. Overall, this project has achieved its objective and this section of the overall water tunnel is capable of providing sufficient fluid flow to the water tunnel test chamber